Analysis Of The Community Satisfaction Index On Public Services In The Village Of Kayu Kunyit, South Bengkulu District - Diana, Diana; Anggriani, Ida; Fitriano, Yun (Jurnal Ekonomi, Manajemen, Akuntansi, 2025)
The Public Satisfaction Index (PSI) is an evaluation instrument used to measure the level of public satisfaction with the quality of public services. This assessment is carried out by comparing public expectations and the reality of the services received. This study aims to analyze the Public Satisfaction Index of public services in Kayu Kunyit Village, Manna District, South Bengkulu Regency. The method used is quantitative research with a descriptive approach using a survey as a data collection technique. The research sample consisted of 150 respondents selected using the Accidental Sampling technique. The data were analyzed using the Public Satisfaction Index (PSI) method in accordance with the Regulation of the Minister of State Apparatus Empowerment and Bureaucratic Reform Number 14 of 2017. The results of the study showed that the value of the PSI of public services in Kayu Kunyit Village was 77.69, which was included in the good category (service quality B). Of the nine assessment elements, behavior and complaint handling received the highest scores, while the completion time and competence of the implementers were elements that still needed to be improved. Overall, the community is satisfied with the services provided, but it is suggested that there be improvements, especially in terms of time efficiency and increasing the competence of officers so that the quality of service can continue to be improved.